Are higher education institutions delivering customer satisfaction? - de Jager, Johan W de Jager; Jan, Muhammad Tahir; Hebblethwaite, Denisa (Australian and New Zealand Academy of Management (ANZAM), 2015)
Higher education institutions are realising the importance of a customer centred approach to survival in the face of increased domestic competition and the globalisation of higher education. The objective of the study is to determine the impact of different variables on customer satisfaction in the higher education sector. More explicitly, this study aims to identify the effects of: support facilities and infrastructure; location and access; and image and marketing on customer satisfaction. A random sample of 390 students was chosen. A review of the structural model indicates that only the causal link between ‘support facilities and infrastructure’ and customer satisfaction can be supported statistically.